Internal Control Analysis towards the Accounts Receivable Accounting System at STIAMI Institute - Iin Andrayanti (Yayasan Ilomata, 2019)
This research aims to reveal how internal control of the accounts receivable system, obstacles faced on the internal control applied, and the endeavors made to reduce it at STIAMI Institute. This research use descriptive-analytical methods to determine the implementation of internal control and account receivable system. Based on the result of the research, internal control towards the account receivable accounting system implemented on STIAMI is quite efficient, indicated by the independence of the audit committee or the internal supervisory unit (ISU) in which are right under the head of STIAMI auspices. In addition, STIAMI's management has applied basic concepts and principles of internal control. In STIAMI internal control activities, it is better to enforce the functions and centralization of the online system so that the operations and financial statement presentation can run effectively and efficiently.